(3ebOeI aj CSGdjH GdESJOdGd GdEMUGFj hGdJfHD (B/s - (3MSf, EeJKGd eMeOs; (3GdYWGQ, dHjHI MSH GdfHj s ((3GdGScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2012)
(3JhRjYGJ GdeYGjfI(B- (3JbOjQ eYGde GdeLJeY(B- (3ENJHGQGJ GdaQhV GdEMUGFjI(B- (3CSGdjH GdESJOdGd GdEMUGFj ddebGQfI Hjf eYGde eLJeYjf(B- (3JMdjd GdJHGjf(B- (3GdESJOdGd GdEMUGFj HGSJNOGe CSdhH cG(B2 - (3GdEQJHGW GdNWj Hjf GdXhGgQs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdESJOdGdjs; (3GdJfHDs